Microfluidics and Microfabrication - Chakraborty, Suman; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
Microfluidics and Microfabrication discusses the interconnect between microfluidics, microfabrication and the life sciences. Specifically, this includes fundamental aspects of fluid mechanics in micro-scale and nano-scale confinements and microfabrication. Material is also presented discussing micro-textured engineered surfaces, high-performance AFM probe-based, micro-grooving processes, fabrication with metals and polymers in bio-micromanipulation and microfluidic applications. Editor Suman Chakraborty, Professor at IIT Kharagpur, India, brings together leading minds in both fields who also: Cover the fundamentals of microfluidics in a manner accessible to multi-disciplinary researchers, with a balance of mathematical details and physical principles Discuss the explicit interconnection between microfluiodics and microfabrication from an application perspective Detail the amalgamation of microfluidics with life sciences Microfluidics and Microfabrication is an ideal book for researchers, engineers and senior-level graduate students interested in learning more about the two fields.
Microfluidic Transport and Micro-scale Flow Physics: An Overview -- Mathematical Modeling of Electrokinetic Effects in Micro and Nano Fluidics -- Microscale Transport Processes and Interfacial Force Field Characterization in Micro-cooling Devices -- Bio-Microfluidics: Overview -- Perspectives of Micro and Nanofabrication of Carbon for Electrochemical and Microfluidic Applications -- Mechanical Micromanufacturing: An Overview -- Bio-Inspired Adhesion and Adhesives: Controlling Adhesion by Micro-Nano Structuring of Soft Surfaces -- Molecular Simulation: Can it Help in the Development of Micro and Nano Devices? -- Fabrication of Spring Steel and PDMS Grippers for the Micromanipulation of Biological Cells.
Keywords: Engineering; Electronics; Engineering; Nanotechnology and Microengineering; Electronics and Microelectronics, Instrumentation; Fluid- and Aerodynamics